The temporal stability of the variability in apparent soil electrical conductivity - Medeiros, Wilker Nunes (2016)
Apparent soil electrical conductivity (ECa) measurements can be used for crop management in precision agriculture. However, ECa is a soil attribute that presents spatial and temporal variability. It is affected by a group of factors that act simultaneously on the soil, such as the soil texture, moisture content, organic matter content and ionic concentrations in the soil solution, which complicates analysis. For soil and crop management, it is important to determine whether the pattern of the ECa spatial variability changes over time. Thus, ECa measurements have the potential for delimiting management zones that are stable over time. The objective of this work was to determine whether the spatial variability pattern of ECa is maintained over time and under different soil conditions. To this end, the ECa was measured at different soil depths using a portable sensor on two crop fields. The first step was to measure and generate an ECa map for each area. By defining a path with the maximum ECa variability, 50 sampling points were located on each field. The ECa values were measured on 20 different dates in the 0 - 20 cm, 0 - 40 cm and 0 - 60 cm soil layers. The soil water content was measured at the same points in the 0 - 20 cm layer on the same dates. The temporal stability of the ECa was analyzed using spatial and temporal variability maps, a correlation analysis and a coefficient of variation over time for each field. In both areas, the ECa exhibited temporal stability in the spatial pattern variability at the three evaluated depths, even though the soil water content values changed on each date. ECa determination presents an important alternative for mapping agricultural fields for crop management in precision agricultural systems.